Applied Future Tenses and Taxonomy Grammatical Error on Writing English English Paragraph of Future Dream - Edi Purnama (Universitas Cokroaminoto Palopo, 2022)
This research aims on how to find the result of students’ ability in applied future tenses in writing English paragraph of future dream not only to measure the average of element sentences paragraph but also to know the percentage taxonomy in grammatical error so that the problem of learning process in writing English can be updated. This research used Descriptive qualitative to collect selected data from students’ written. There are three applied grand theories in this research in which they are Oshima and Houge (2006) In Writing and Azar (2002) in Grammar as well as Dulay (1982) in Error analysis. It took us one semester to take the data which were taken from 3 universities, as many as 199 students. Their subject study: University A is in Computer Engineering and System Informatics as many as 70 students and data taken is from final test, University B is in Economics Management as many as 60 students and the data taken is from assignment of meeting 7. University C is in Management Informatics and in System Informatics as many as 71students and data taken is from final test. They were given the same as questions. The result of the research in the surface of the average of element paragraph writing is divided into four main categories in this specific instance: The first is in simple sentence (10,57) and the second is in compound sentence (6,90) thus the third is in complex sentence (3.70 afterward the fourth is in grammatical error (2,71) meanwhile In the surface of percentage of grammatical error is divided into: The lowest point in grammatical error students’ problem is in Addition (AD) 37% and the second lowest point in grammatical error students is in Omission (OM) 30%. The third lowest point is in Misformation(MF) 27% and The fourth lowest is in Misordering (MO) 6%.